Perlindungan Environmental Rights untuk Korban Dampak Kerusakan Lingkungan Studi Kasus: Kebakaran Rutan Indonesia (1998) dan Luapan Lumpur Sidoardjo-Lapindo Brantas (2006) - Linda Yanti Sulistiawati (Mimbar Hukum - Fakultas Hukum Universitas Gadjah Mada, 2009)
It is clear that environmental rights are among The most important basic rights in human’s life. Although embedded in more than several international treaties, there is yet an independent treary which focusing solely an environmental rights. This is very unfortunate to developing countries such as Indonesia, whose most environmental problems are caused by human and/or development activities and with victim improtected of their environmemal rights. This research unfolds two case studies in Indonesia regarding to be protection of three basic rights: the right to be free from hunger; the right to security and the right to health. In principle these case studies pictures enviromnental rights protection in Indonesia, which is already protected on the legal basis, but lack of implementation in the field.